Outcomes of Posterior Malleolar Fixation in Ankle Fractures in A Major Trauma Centre. Issue 1 (January 2022) - Bua, Nelson; Jeyaseelan, Luckshmana A.; Parker, Lee; Trockels, Amaury; Sohrabi, Catrin; Vris, Alexandros; Heidari, Nima; Romans, Francesc Malagelada
Category: Ankle; Trauma Introduction/Purpose: Ongoing controversy exists over the indications and benefits of posterior malleolar fixation in ankle fractures. These injuries require careful evaluation of the bony and ligamentous structures with theoretical benefits of posterior malleolar fixation now widely accepted as restoration of articular congruity, restoration of fibular length and stabilisation of the syndesmosis. Surgical and patient report outcomes are varied in the literature with analysis limited by the lack of standardisation in functional outcomes and small patient populations. Posterior malleolar fixation does extend operative time and potentially increases complication rate. The aim of this pragmatic study was to evaluate the outcomes of posterior malleolar fracture fixation in the setting of a major trauma centre. Our hypothesis is that posterior malleolus fixation leads to improved clinical outcomes. Methods: A total of 320 patients were identified with operatively treated ankle fractures involving a posterior malleolus component, between January 2012 and January 2018, with minimum 2 year follow-up. Patient electronic records were assessed for demographic data including age, gender, mechanism of injury, co-morbidities and smoking status. Pre-operative imaging, including CT was used to evaluate the nature of the injury and classify the posterior malleolar fracture according to the Mason classification. One hundred and sixty patients underwent posterior malleolus fixation as part of their surgery and 160 patients did not. The Manchester-Oxford Foot Questionnaire (MOXFQ) at final follow-up, was the primary patient outcome measure.Complications were noted to be minor (superficial infection or delayed wound healing) or major (DVT/PE, deep infection, chronic regional pain syndrome (CRPS), arthrofibrosis, further intervention for post-traumatic arthritis, hardware failure or irritation). All cause reoperation rates were also noted. Results: Fixation of the posterior malleolus was associated with a statistically significant improvement in patient outcomes. Mean MOXFQ score in the unfixed posterior malleolus group was 24.03 (0 - 62), compared to 20.10 (0 - 67) in the fixed posterior malleolus group (p =0.04). Outcomes were worse with increasing size of posterior malleolar fragment. When compared with either posterior malleolus fixation alone or syndesmotic stabilisation alone, poorer outcomes were seen when the posterior malleolus fixed with additional syndesmotic stabilisation, with mean MOXFQ scores of 21.73 (0-60), p =0.057. Metalwork-related issues were higher in the posterior malleolus fixed group (24/160 (15%) versus 10/160 (6.2%), p=0.03). Re-operation rate was double (34/160 (21.2%) vs 16/160 (10%), p = 0.03). The main cause of this was hardware related issues. Conclusion: This pragmatic study is one of the largest published series that assesses patient reported outcomes in posterior malleolar fixation. The key finding is that posterior malleolar fixation is associated with a statistically significant improvement in patient reported outcome scores. However, the overall complication rate was 10.7% higher in the fixation group and the risk of reoperation was over double. Further research should focus on high quality randomised controlled trials with long term follow-up to assess long term impacts of this complex ankle injury pattern.